Colletotrichum siamense causing anthracnose in postharvest of ‘Hass’ avocado - Herrera-González, Juan Antonio; Bautista-Baños, Silvia; Serrano, Mario; Ramos-Bell, Surelys; Gutiérrez-Martínez, Porfirio (Revista Mexicana de Ciencias Agrícolas, 2024)
Mexico is the leading producer and exporter of avocados in the world. The main producing area is the Central Pacific Region of Mexico (Jalisco, Michoacán, and Nayarit), where 96% of the national production is harvested. Anthracnose in avocado postharvest can reach between 20 and 80% losses due to the deterioration of the quality of the avocado fruit. The objective of the research was to diagnose the causative agent of anthracnose of avocado postharvest in the Central Pacific Region of Mexico, the study was conducted between 2019 and 2020. Completely healthy avocado fruits were sampled and pathogenic fungi that cause anthracnose were isolated, a morphological, molecular, and phylogenetic identification was carried out, as well as their development under fungicide stress. Morphological characteristics indicated that the fungus that causes anthracnose in postharvest belongs to Colletotrichum gloeosporioides sensu lato. Molecular and phylogenetic tests identified the fungi as Colletotrichum siamense, an endophytic fungus capable of existing in two conditions of fruit life (pre- and postharvest). This fungus under fungicide stress remains in an inactive state in response until its effect wears off.
Keywords: Persea americana Miller; Synthetic fungicides; Postharvest